Economic-Financial Analysis of Municipal Solid Waste Recycling In Brazil: a Case Study of a Recycling Cooperative - Silva, Michele Barros de Deus Chuquel da; Martins, Bianca Rocha; Simioni, Flávio José (Fronteira: Journal of Social, Technological and Environmental Science, 2023)
Economic development and the growth of industrialization have contributed to an increase in the generation of solid waste in urban areas. Municipal solid waste recycling cooperatives (MSWRCs) provide environmental benefits as well as better working and living conditions for waste pickers. This article analyzes the economic viability of a MSWRC in Brazil using economic-financial indicators, with data from September 2021. Economic viability was analyzed considering the net present value (NPV), annualized net present value (ANPV), internal rate of return (IRR), benefit-cost ratio (BCR) and discounted payback with a minimum attractiveness return rate (MARR) of 3% per year. Financial risk was evaluated using the Monte Carlo method, considering three scenarios for income and the remuneration of cooperative members. The base scenario (operating conditions prioritizing the remuneration of the members of the cooperative) places the future sustainability of the business at risk. Variations in the revenue from the sale of recyclable materials and in the remuneration of cooperative members exert a considerable influence on economic and financial indicators, representing a high risk of losses (between 23% and 26.6%). In conclusion, the future sustainability of MSWRCs depends on strategies for increasing revenue whether through the enterprises themselves or through public policies. The need for the better remuneration of cooperative members constitutes a challenge for management due to the need to make investments in the maintenance and growth of the production unit.